Austenitic stainless steel bonded hard alloy and preparation method thereof
By using austenitic stainless steel junction carbide, combined with the formation of TiC-Mo and TiC-WC solid solution, the problem of poor wear resistance of existing steel junction carbide in high temperature and high corrosion environments is solved, and a new efficient and durable material is realized, suitable for the preparation of core components of double screw extruders.
Patent Information
- Application Number
- CN202411922669.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-25
AI Technical Summary
When used in high-temperature and high-corrosion environments, existing steel junction carbides have poor wear resistance and frequent mold unloading and installation debugging, resulting in low production efficiency, high cost and limited use range.
Austenitic stainless steel steel junction carbide is used, containing 35-50% titanium carbide powder, 10-20% tungsten carbide powder, 30-55% 304 austenitic stainless steel powder and 2-5% molybdenum powder, and is prepared by vacuum sintering process to form TiC-Mo and TiC-WC solid solution, improving the density and wear resistance of the alloy.
The high-temperature thermal stability, oxidation resistance and corrosion resistance of the alloy are achieved, and its strength, wear resistance and toughness are significantly improved. The life span is more than 3 times higher than that of conventional materials. It is suitable for the preparation of core components of double-spiral extruders in plastic engineering machinery.
Smart Images

Figure CN119800195A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel-bonded hard alloy, and in particular to an austenitic stainless steel steel-bonded hard alloy and a preparation method thereof. Background Art
[0002] The twin-screw extruder of plastic engineering machinery is the main equipment for processing and manufacturing engineering plastics. Its working environment is to crush, stir, and convey high-viscosity and high-strength engineering plastics at a high temperature of 200-300℃. In addition to high temperature, it is also highly corrosive and has a harsh working environment. The core components of the extruder are in contact with high-temperature engineering plastics, including the twin-screw barrel and the screw block for crushing, stirring, and conveying installed on the screw. This requires these two core components to have the characteristics of high corrosion resistance, high wear resistance, high-temperature thermal stability, high toughness, and high strength. The screw is usually larger than 2m, and can only use high-speed steel, special steel, or stainless steel materials prepared by pyrometallurgy with poor rigidity. In order to prevent the screw from bending and deformation, the screw block installed on it is also required to have the characteristics of light weight. At present, the double-screw barrel and spiral block in the industry are mainly made of Stellite alloy, nickel-based alloy, high-speed steel, stainless steel and other materials. However, these three materials have poor wear resistance and require frequent mold unloading, installation and debugging, resulting in low production efficiency. They have been criticized by the industry. Among them, Stellite alloy and nickel-based alloy have the problem of high cost and limited scope of use, and high-speed steel has the problem of poor corrosion resistance.
[0003] Chinese patent CN112301295B provides a steel-bonded cemented carbide and its preparation method and application, wherein the main components are 35-45% titanium carbide, 40-50% reduced iron powder, 2-5% reduced molybdenum powder, 2-5% reduced nickel powder, 10-15% manganese powder and 0-3% chromium powder, that is, the Cr content only accounts for 0-5.45% of the bonding phase other than the hard phase, which is far less than the 13% required for steel to meet the requirements of stainless and oxidation resistance, and can only be used in a normal temperature and non-corrosive environment; Chinese patent CN103215483B discloses a steel-rolled High-strength industrial cutting tools contain 5-10% carbon powder in their composition. During use, the carbon element easily combines with oxygen to form carbonates, resulting in the alloy lacking a protective layer and being easily oxidized and corroded. Chinese patent CN103114232A discloses that La2O3 can react with impurities and oxide films on the interface of metal powders to purify the interface, thereby improving the wettability of the bonding phase and the hard phase and increasing the compactness of the alloy. However, the Ni content in its composition is only 1.0-2.0%, which is insufficient to wet 48-50% TiC to provide sufficient toughness. Summary of the invention
[0004] In view of the above technical problems in the related art, the present invention provides an austenitic stainless steel bonded cemented carbide and a preparation method thereof, which can solve the above problems.
[0005] To achieve the above technical objectives, the technical solution of the present invention is implemented as follows: An austenitic stainless steel bonded hard alloy comprises the following components in percentage by mass: 35-50% titanium carbide powder, 10-20% tungsten carbide powder, 30-55% 304 austenitic stainless steel powder, and 2-5% molybdenum powder, wherein the FSSS particle size of the titanium carbide powder is 0.8-3.0 μm, the FSSS particle size of the tungsten carbide powder is 0.4-3.0 μm, the FSSS particle size of the 304 austenitic stainless steel powder is 1.0-3.0 μm, and the FSSS particle size of the molybdenum powder is 2.0-5.0 μm.
[0006] Furthermore, the mass proportion of titanium carbide fine powder with FSSS particle size less than 1 μm in the entire titanium carbide powder is ≥20%.
[0007] Furthermore, the composition of 304 austenitic stainless steel is Fe x Ni y Cr z , the subscripts x, y, and z are the mass percentages of the elements, where y is greater than 8 and z is greater than 17.5.
[0008] A method for preparing austenitic stainless steel bonded hard alloy comprises the following steps: S1. Weigh titanium carbide powder, tungsten carbide powder, 304 austenitic stainless steel powder and molybdenum powder, mix and ball-mill with paraffin powder and alcohol medium to obtain a mixture; S2, drying the obtained mixed material; S3, pressing the dried mixture to obtain a compact; S4. Vacuum sintering the mixed material compact in S3 at 1350-1480° C. to remove the wax molding agent and densify the alloy, thereby obtaining an austenitic stainless steel bonded carbide containing both TiC-Mo solid solution and TiC-WC solid solution.
[0009] Furthermore, in step S1, when weighing a mass M1 of titanium carbide powder, a mass M2 of tungsten carbide powder, a mass M3 of 304 austenitic stainless steel powder, and a mass M4 of molybdenum powder, a mass M5 of Co powder is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, wherein M5≤10% (M1+M2+M3+M4).
[0010] Furthermore, in step S1, when weighing a mass M1 of titanium carbide powder, a mass M2 of tungsten carbide powder, a mass M3 of 304 austenitic stainless steel powder, and a mass M4 of molybdenum powder, a mass M6 of Ni powder is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, wherein M6≤10% (M1+M2+M3+M4).
[0011] Furthermore, in step S1, when weighing mass M1 of titanium carbide powder, mass M2 of tungsten carbide powder, mass M3 of 304 austenitic stainless steel powder and mass M4 of molybdenum powder, mass M7 of La2O3 powder and the like is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, wherein M7≤0.5% (M1+M2+M3+M4).
[0012] Furthermore, the paraffin powder is 3.0-5.0% of the total mass of the titanium carbide powder, the tungsten carbide powder, the 304 austenitic stainless steel powder and the molybdenum powder.
[0013] Beneficial effects of the invention: the austenitic stainless steel bonded carbide of the present application not only has good oxidation resistance, corrosion resistance, and high-temperature thermal stability, but is also a new material with higher strength, wear resistance, and toughness. Its service life is more than 3 times longer than that of conventional materials. It is suitable for the preparation of core components of twin-screw extruders of plastic engineering machinery. At the same time, the preparation process of this material is equivalent to that of conventional cemented carbide, and it has the characteristics of low cost, controllable quality, and mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] The present invention is further described in detail below with reference to the accompanying drawings.
[0016] Figure 1 is a metallographic photograph of a steel-bonded cemented carbide according to Example 2 of the present invention; Figure 2 is a metallographic photograph of a steel-bonded cemented carbide according to Example 3 of the present invention; Figure 3 is a metallographic photograph of a steel-bonded cemented carbide according to Example 1 of the present invention; Figure 4 It is a metallographic photograph of the steel-bonded cemented carbide of Comparative Example 3 of the present invention.
[0017] In the figure (Note: In order to highlight the characteristics of the hard phase, Figure 1 , Figure 2 , Figure 3 , Figure 4 All were taken after removing the adhesive phase): 1. TiC-Mo solid solution; 2. TiC grains; 3. TiC-WC solid solution. DETAILED DESCRIPTION
[0018] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0019] Embodiment 1: Titanium carbide powder with FSSS particle size of 2.5 μm, tungsten carbide powder with FSSS particle size of 1.5 μm, 304 austenitic stainless steel powder with FSSS particle size of 2.5 μm, and molybdenum powder with FSSS particle size of 3.5 μm were selected. The fine powder with FSSS particle size less than 1 μm in the TiC powder accounted for 25%.
[0020] The raw materials are as follows: titanium carbide powder accounts for 40% (the mass of titanium carbide powder is 40kg, of which FSSS fine powder with a particle size of less than 1μm accounts for 40*25%=10kg); tungsten carbide powder accounts for 15% (the mass of tungsten carbide powder is 15kg); 304 austenitic stainless steel powder accounts for 41% (the mass of 304 austenitic stainless steel powder is 41kg); molybdenum powder accounts for 4.0% (the mass of molybdenum powder is 4kg); the total weight of the powder is 100kg. Then, an additional paraffin powder (4.2kg) accounting for 4.2% of the mass is weighed, mixed with 45L alcohol medium at a ball-to-material ratio of 3:1, and ball-milled for 50 hours, and then vacuum dried to obtain a mixture.
[0021] The dried mixture is pressed and sintered at 1430°C in vacuum to obtain an austenitic stainless steel bonded carbide of the present invention. The relevant properties are shown in Table 1 and the organizational structure is shown in Table 2. Figure 3 .
[0022] According to actual use tests, the service life of a single die of a twin-screw extruder for plastic engineering machinery is three times that of a die made of high-speed steel.
[0023] Embodiment 2: Titanium carbide powder with FSSS particle size of 2.5 μm, tungsten carbide powder with FSSS particle size of 1.5 μm, 304 austenitic stainless steel powder with FSSS particle size of 2.8 μm, cobalt powder with FSSS particle size of 0.8 μm, molybdenum powder with FSSS particle size of 3.5 μm and lanthanum oxide powder with FSSS particle size of 0.8 μm were selected. The fine powder with FSSS particle size less than 1 μm in the TiC powder accounted for 25%.
[0024] The mass proportions of the raw materials are as follows: titanium carbide powder accounts for 40% by mass; tungsten carbide powder accounts for 20% by mass; 304 austenitic stainless steel powder accounts for 30.6% by mass; cobalt powder accounts for 5.0% by mass; molybdenum powder accounts for 4% by mass; lanthanum oxide powder accounts for 0.4% by mass, and the total weight of the powder is 100 kg. An additional paraffin powder accounting for 3.8% by mass is weighed, mixed with 38 L of alcohol medium at a ball-to-material ratio of 4.5:1, and ball-milled for 25 hours, and then vacuum dried to obtain a mixture.
[0025] The dried mixture is pressed and sintered at 1410°C in vacuum to obtain an austenitic stainless steel bonded carbide of the present invention. The relevant properties are shown in Table 1 and the organizational structure is shown in Table 2. Figure 1 .
[0026] According to actual use tests, the service life of a single die of a twin-screw extruder for plastic engineering machinery is 6 times that of a die made of high-speed steel.
[0027] Embodiment 3: FSSS 2.0μm titanium carbide powder, FSSS 1.5μm tungsten carbide powder, FSSS 2.5μm 304 austenitic stainless steel powder, FSSS 1.2μm cobalt powder, FSSS 3.5μm molybdenum powder and FSSS 0.8μm lanthanum oxide powder were selected. The fine powder with FSSS particle size less than 1μm accounted for 35% of the TiC powder.
[0028] The raw materials are as follows: titanium carbide powder accounts for 40% by weight; tungsten carbide powder accounts for 15% by weight; 304 austenitic stainless steel powder accounts for 30.65% by weight; cobalt powder accounts for 10.0% by weight; molybdenum powder accounts for 4.0% by weight; and lanthanum oxide powder accounts for 0.35% by weight. The total weight of the powder is 100 kg, and an additional 4.0% paraffin powder is weighed and mixed with 42L of alcohol medium at a ball-to-material ratio of 4:1 for 40 hours, and then vacuum dried to obtain a mixture.
[0029] The dried mixture is pressed and sintered at 1430°C in vacuum to obtain an austenitic stainless steel bonded carbide of the present invention. The relevant properties are shown in Table 1 and the organizational structure is shown in Table 2. Figure 2 .
[0030] According to actual use tests, the service life of a single die of a twin-screw extruder for plastic engineering machinery is five times that of a die made of high-speed steel.
[0031] Comparative Example 1: The properties of 304 austenitic stainless steel purchased on the market are shown in Table 1.
[0032] Comparative Example 2: The properties of high speed steel W6Mo5Cr4V2 are shown in Table 1.
[0033] Comparative Example 3: Titanium carbide powder with FSSS particle size of 2.5 μm, 304 austenitic stainless steel powder with FSSS particle size of 2.5 μm, and molybdenum powder with FSSS particle size of 3.5 μm were selected. The fine powder with FSSS particle size less than 1 μm in the TiC powder accounted for 25%.
[0034] The raw materials are as follows: titanium carbide powder accounts for 55% of the mass; 304 austenitic stainless steel powder accounts for 41% of the mass; molybdenum powder accounts for 4.0% of the mass; the total weight of the powder is 100kg. Then, an additional 4.2% of paraffin powder is weighed, mixed with 45L of alcohol medium at a ball-to-material ratio of 3:1, ball-milled for 50 hours, and then vacuum dried to obtain a mixture; The dried mixture is pressed and sintered at 1430°C in vacuum to obtain an austenitic stainless steel bonded carbide with a density of only 95%. The relevant properties are shown in Table 1 and the organizational structure is shown in Figure 4 .
[0035] In the above examples and comparative examples, the composition of 304 austenitic stainless steel is Fe 71 Ni 11 Cr 18 (Subscripts are mass percentages of elements).
[0036] Cracking during actual use test.
[0037] Table 1 Corrosion test conditions: The samples of the same appearance size were immersed in hydrochloric acid with a pH value of 2.0 for 48 hours and the results were measured. From the results, it can be seen that Example 1, Example 2, and Example 3 have very excellent corrosion resistance, and the corrosion rate is only 3.2% to 3.6% of that of high-speed steel W6Mo5Cr4V2.
[0038] In summary, the present invention provides an austenitic stainless steel bonded carbide, which is added with TiC, WC and Mo. In the test and production, we found that WC grains can be solid-dissolved with fine TiC particles (such as Figure 1 As shown in the figure, the fine and brittle TiC phase is eliminated, and a TiC-WC solid solution 3 is generated that is finer than the original WC grains, with a size of less than 1.0 μm and a rounded appearance. These solid solutions are evenly and dispersedly distributed in the bonding phase, playing the role of pinning and strengthening the bonding phase. At the same time, the fine TiC-WC solid solution 3 itself has a higher resistance to spalling wear. TiC-Mo solid solution 1 (as shown in the figure) is also generated at the edge of the large TiC grain 2. Figure 1As shown in the figure, the wettability of TiC and the binder phase is improved. Therefore, the austenitic stainless steel bonded carbide of the present invention can obtain higher density, bending strength and wear resistance, and its bending strength can reach more than 1000MPa, and its density can reach more than 98%. In addition, the strength and toughness can be further improved by adding Co, Ni, and La2O3.
[0039] After inspection and actual use tests, it has the same antioxidant, corrosion resistance, and high-temperature thermal stability as austenitic stainless steel, and its service life is more than 3 times longer than that of conventional materials. It is suitable for the preparation of double-screw barrels and screw blocks, core components of double-screw extruders for plastic engineering machinery. At the same time, the preparation process of this material is equivalent to that of conventional cemented carbide, and it has the characteristics of low cost, controllable quality, and mass production.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An austenitic stainless steel bonded carbide, characterized in that: The invention comprises the following components in percentage by mass: 35-50% titanium carbide powder, 10-20% tungsten carbide powder, 30-55% 304 austenitic stainless steel powder, and 2-5% molybdenum powder, wherein the FSSS particle size of the titanium carbide powder is 0.8-3.0 μm, the FSSS particle size of the tungsten carbide powder is 0.4-3.0 μm, the FSSS particle size of the 304 austenitic stainless steel powder is 1.0-3.0 μm, and the FSSS particle size of the molybdenum powder is 2.0-5.0 μm.
2. The austenitic stainless steel bonded carbide according to claim 1, characterized in that: The mass proportion of titanium carbide fine powder with FSSS particle size less than 1 μm in the entire titanium carbide powder is ≥20%.
3. The austenitic stainless steel bonded carbide according to claim 1, characterized in that: The composition of 304 austenitic stainless steel is Fe x Ni y Cr z , the subscripts x, y, and z are the mass percentages of the elements, where y is greater than 8 and z is greater than 17.
5.
4. A method for preparing austenitic stainless steel bonded carbide according to any one of claims 1 to 3, characterized in that: The steps include: S1. Weigh titanium carbide powder, tungsten carbide powder, 304 austenitic stainless steel powder and molybdenum powder, mix and ball-mill with paraffin powder and alcohol medium to obtain a mixture; S2, drying the obtained mixed material; S3, pressing the dried mixture to obtain a compact; S4. Vacuum sintering the mixed material compact in S3 at 1350-1480° C. to remove the wax molding agent and densify the alloy, thereby obtaining an austenitic stainless steel bonded carbide containing both TiC-Mo solid solution and TiC-WC solid solution.
5. The method for preparing austenitic stainless steel bonded hard alloy according to claim 4, characterized in that: In step S1, when weighing mass M1 of titanium carbide powder, mass M2 of tungsten carbide powder, mass M3 of 304 austenitic stainless steel powder and mass M4 of molybdenum powder, mass M5 of Co powder is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, where M5≤10% (M1+M2+M3+M4).
6. The method for preparing austenitic stainless steel bonded hard alloy according to claim 4, characterized in that: In step S1, when weighing mass M1 of titanium carbide powder, mass M2 of tungsten carbide powder, mass M3 of 304 austenitic stainless steel powder and mass M4 of molybdenum powder, mass M6 of Ni powder is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, where M6≤10% (M1+M2+M3+M4).
7. The method for preparing austenitic stainless steel bonded hard alloy according to claim 4, characterized in that: In step S1, when weighing mass M1 of titanium carbide powder, mass M2 of tungsten carbide powder, mass M3 of 304 austenitic stainless steel powder and mass M4 of molybdenum powder, mass M7 of La2O3 powder is weighed to replace the 304 austenitic stainless steel powder to further improve the strength and toughness of the alloy, where M7≤0.5% (M1+M2+M3+M4).
8. The method for preparing austenitic stainless steel bonded hard alloy according to claim 4, characterized in that: The paraffin powder accounts for 3.0-5.0% of the total mass of the titanium carbide powder, the tungsten carbide powder, the 304 austenitic stainless steel powder and the molybdenum powder.
Citation Information
Patent Citations
High-intensity industrial cutter for steel rolling
CN103215483B
A steel-structured cemented carbide, its preparation method and application
CN112301295B
Carbide alloy welding wire or welding rod as well as manufacturing method and application thereof
CN101462206A
Rare-earth modified steel-bonded hard alloy and preparation method
CN103114232A
High-intensity industrial cutter for steel rolling
CN103215483A